A photo-thermal dual-responsive self-healing ionic liquid-amine complex CO2 absorbent and a capturing method and device thereof

CN123024399APending Publication Date: 2026-11-03HUANENG CLEAN ENERGY RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611441123.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing CO2 chemical absorption processes suffer from high regeneration energy consumption, insufficient long-term cycle stability of amine absorbents, difficulty in effectively coupling photothermal materials with liquid absorbents, and the lack of application of dynamic covalent self-healing materials in CO2 liquid absorbent systems, resulting in high system operating costs and poor stability.

Method used

A photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent is adopted. 1-Octyl-3-methylimidazolium thiocyanate converts light energy into heat energy under light irradiation, driving the hydrolysis and recombination of reversible borate ester bonds, thereby realizing the reconstruction of the internal network of the absorbent and CO2 desorption. Combined with the synergistic effect of dynamic covalent amine and active amine, the fluidity and absorption performance are maintained.

Benefits of technology

It significantly reduces regeneration energy consumption, solves the problem of long-term operational stability of absorbents, avoids the sedimentation of solid photothermal particles, maintains the flowability and self-healing ability of absorbents, and achieves efficient CO2 capture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123024399A_ABST
    Figure CN123024399A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of carbon dioxide capture, and discloses a kind of photo-thermal dual-response self-repairing ionic liquid-amine complex CO2 absorbent and its capture method and device.The absorbent includes 1-octyl-3-methyl imidazole thiocyanate, dynamic covalent amine containing o-diphenol group, boric acid or boric acid derivative, active amine and water;Dynamic covalent amine forms reversible borate ester bond through o-diphenol group and boric acid or boric acid derivative.Under light, 1-octyl-3-methyl imidazole thiocyanate converts light energy into heat energy, drives borate ester bond to occur hydrolysis-reformation or ester exchange reaction, realizes network reconstruction and absorption performance recovery.The application also discloses a capture method and continuous flow device using the absorbent.The absorbent has low regeneration energy consumption, good cycle stability, and has photo-thermal response and self-repairing functions, and can maintain good fluidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon dioxide capture technology, specifically relating to a photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent and its capture method and apparatus. Background Technology

[0002] As a major greenhouse gas, carbon dioxide (CO2) control and emission reduction are crucial for actively addressing global climate change. Carbon capture, utilization, and storage (CCUS) technology is considered one of the important technological approaches to achieving deep carbon emission reduction, especially decarbonization of industries with difficult emission reduction requirements. In the carbon capture process, chemical absorption using organic amines as absorbents is one of the more mature and widely used CO2 capture technologies due to its advantages of fast absorption rate and good selectivity.

[0003] In existing CO2 chemical absorption processes, amine absorbents, such as ethanolamine (MEA), diethanolamine (DEA), N-methyldiethanolamine (MDEA), piperazine (PZ), and 2-amino-2-methyl-1-propanol (AMP), mainly rely on low-temperature absorption in the absorption tower and external steam heating and regeneration in the desorption tower for a cyclic operation. Although this type of system is technologically mature, it still faces the following technical challenges: First, regeneration energy consumption is high. Traditional amine solutions require heating a large amount of water and amine solution to a relatively high temperature (usually around 110-130°C) to achieve effective CO2 desorption. The heat is mainly provided by external steam or electric heating, resulting in regeneration energy consumption accounting for 60% to 80% of the total operating cost of the carbon capture process. How to reduce regeneration energy consumption and make full use of low-grade renewable energy sources such as sunlight is one of the key issues that urgently need to be addressed in current amine-based carbon capture technology.

[0004] Secondly, amino acid amines such as MEA are prone to degradation during long-term operation. O2 can promote oxidative degradation, while high temperature and CO2 load can promote thermal degradation, and SO2 can promote degradation. x Impurities in flue gas, such as NO2, can also lead to the accumulation of heat-stable salts, resulting in problems such as amine loss, decreased absorption capacity, and accelerated corrosion.

[0005] Third, current research on photothermal CO2 regeneration largely employs solid adsorbents, while embedded photothermal schemes in liquid absorbents primarily rely on solid nanoparticle dispersion. Although such systems can achieve photothermal conversion within the liquid phase, they still face challenges in long-term dispersion stability, cyclic operation, and engineering transport. Existing photothermal solid adsorbents can utilize materials such as carbon black, carbon nanotubes, and titanium nitride to convert light energy into heat energy for CO2 desorption. For example, literature reports that ammoniated silica-carbon black aerogel can achieve CO2 desorption at 2.0 kW / m³. 2Under LED light source irradiation, the temperature can be rapidly raised to approximately 70°C, with a CO2 desorption efficiency of about 80%. However, this type of approach mainly targets solid adsorbents, and liquid amine absorbents still lack designs for flowable, recyclable, and self-healing endogenous photothermal components. Furthermore, although some studies have attempted to disperse photothermal conversion materials such as carbon-based nanomaterials in amine solutions or eutectic solvents to form nanofluids, utilizing their photothermal conversion properties to achieve solar-driven CO2 regeneration, solid nanoparticles in liquid systems suffer from sedimentation, agglomeration, and poor long-term operational stability, limiting their industrial application.

[0006] Fourth, conventional ionic liquid-amine complex systems typically only focus on CO2 solubility, volatility, viscosity, or phase equilibrium, lacking dynamic covalent self-repair capabilities. In recent years, researchers have attempted to introduce ionic liquids into amine absorbent systems to improve absorption performance. For example, patent document CN116651148A discloses a low-temperature self-extraction regeneration functionalized ionic liquid CO2 absorbent. This absorbent uses di-n-butylamine imidazole ([DBAH][Im]) functionalized ionic liquid as the main absorbent, utilizing the group interactions between the absorbent's anions and cations to give the absorbed products a low desorption free energy, thereby achieving low-temperature regeneration and reducing energy consumption. Simultaneously, this absorbent also exhibits self-extraction characteristics; that is, during regeneration, the desorbed ionic liquid collects at the top of the solution to form an organic phase. This organic phase acts as a self-extracting agent to extract subsequently regenerated ionic liquid from the aqueous phase, thereby promoting desorption and increasing the desorption rate. However, this type of system still relies on an external heat source (such as a heating device) to provide the heat required for regeneration and does not involve the introduction of a photothermal conversion mechanism. In addition, although there have been reports on the CO2 solubility of thiocyanate imidazole ionic liquids (such as [OMIM][SCN]), for example, the CO2 solubility in nitrate and thiocyanate ionic liquids was measured under conditions of 298.15~333.15K and a maximum of 4.5MPa, such studies have not constructed a self-circulating absorbent system of "light-triggered network reconstruction ~ dark absorption".

[0007] Fifth, dynamic covalent self-healing materials are mostly used in gels, elastomers, coatings, or solid materials, and have not yet been fully adapted to CO2 liquid absorbent systems. The chemical principle that organoboronic acid groups (such as phenylboronic acid groups) can form reversible borate ester dynamic covalent bonds (B–O) with vicinal or cis-diols has been widely used in self-healing hydrogels, elastomers, and organic gels. Furthermore, borate ester bonds can achieve network recombination through mechanisms such as hydrolysis-re-esterification and transesterification. However, these dynamic bonds are generally not designed for fluid CO2 amine liquids. Directly introducing them into amine liquid systems can lead to problems such as easy gelation, amine group encapsulation, increased viscosity, and decreased mass transfer.

[0008] In summary, there is an urgent need in the existing technology for a novel absorbent system that can introduce an endogenous heat source that can be driven by light into the liquid absorbent, while having dynamic network reconstruction capability and maintaining good fluidity and CO2 absorption performance. Summary of the Invention

[0009] The purpose of this invention is to provide a photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent and its capture method and apparatus, which solves the technical problems of high regeneration energy consumption and insufficient long-term cycle stability of existing amine CO2 absorbents, as well as the difficulty of effectively coupling existing photothermal materials with the internal chemical processes of liquid absorbents, and the fact that dynamic covalent self-healing materials have not yet been converted into CO2 liquid absorbent systems.

[0010] This invention is achieved through the following technical solution: This invention discloses a photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent, comprising: 1-octyl-3-methylimidazolium thiocyanate, a dynamic covalent amine containing a catechol group, boric acid or a boric acid derivative, an active amine, and water; The dynamic covalent amine forms a reversible borate bond with boric acid or boric acid derivatives through the catechol group; The 1-octyl-3-methylimidazolium thiocyanate converts light energy into heat energy under illumination to drive the reversible borate ester bond to undergo hydrolysis-reformation or transesterification reactions, thereby achieving internal network reconstruction of the absorbent and restoration of CO2 absorption performance.

[0011] Furthermore, the absorbent comprises, by weight percentage: 1-Octyl-3-methylimidazolium thiocyanate: 2~40 wt% Dynamic covalent amines: 0.1~20 wt% Boric acid or boric acid derivatives: 0.02~10 wt% Active amines: 5~35 wt% Water: 20~80 wt% Additives: 0~5 wt%.

[0012] Furthermore, the absorbent comprises, by weight percentage: 1-Octyl-3-methylimidazolium thiocyanate: 5~25 wt% Dynamic covalent amines: 1~10 wt% Boric acid or boric acid derivatives: 0.1~3 wt% Active amine: 15~25 wt% Water: 35~65 wt% Additives: 0.01~2 wt%.

[0013] Furthermore, the molar ratio (B / Cat) of boron to catechol groups in boric acid or boric acid derivatives is 0.05 to 1.20; The molar ratio of the dynamic covalent amine to the active amine is 0.005~0.30.

[0014] Furthermore, the additive is selected from one or more of antioxidants, metal ion chelators, corrosion inhibitors, defoamers, pH buffers, or photothermal enhancers; The dynamic covalent amine is N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine.

[0015] Furthermore, the pH value of the absorbent is 8.5~11.5; The absorbent has a viscosity of ≤80 mPa·s at 40°C.

[0016] Furthermore, the active amine is one or more of ethanolamine, diethanolamine, N-methyldiethanolamine, 2-amino-2-methyl-1-propanol, and piperazine.

[0017] The present invention also discloses a CO2 capture method, comprising the following steps: (1) Under dark or light-proof conditions, the absorbent is brought into contact with CO2-containing gas at 20~45℃ to absorb CO2 and obtain a CO2-rich absorbent; (2) The CO2-rich absorbent is placed under light conditions to cause 1-octyl-3-methylimidazolium thiocyanate to undergo photothermal conversion and be heated to 60~95℃, thereby driving the reconstruction of borate ester bonds and releasing some CO2. (3) Cool the absorbent after releasing CO2 to 20~45℃ and return to step (1) for recycling.

[0018] Furthermore, in step (2), the illumination intensity is 500~1500 W / m². 2 The illumination time is 1~60min, and the liquid layer thickness of the CO2-rich absorbent is 0.5~10 mm.

[0019] The present invention also discloses a continuous flow absorption-photoremediation / regeneration device for implementing the CO2 capture method, comprising: The light-shielding absorption tower is used to make the absorbent come into countercurrent contact with CO2-containing gas, and to absorb CO2 at 20~45℃ under dark or light-shielding conditions. A rich liquid buffer tank, connected to the bottom of the light-shielding absorption tower, is used to receive CO2-rich absorbent; A transparent light-induced repair / regenerator is connected to the outlet of the rich liquid buffer tank. It is used to heat the CO2-rich absorbent to 60~95°C under light conditions, while simultaneously completing CO2 desorption and internal network reconstruction of the absorbent. A CO2 separator, connected to the gas outlet of the transparent light-induced repair / regenerator, is used to separate and collect the desorbed CO2; A lean liquid cooler, connected to the liquid outlet of the transparent light-induced repair / regeneration device, is used to cool the regenerated absorbent to 20~45°C. A circulating pump, connected between the outlet of the lean liquid cooler and the top of the light-shielding absorption tower, is used to return the cooled absorbent to the light-shielding absorption tower for recycling.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects: The purpose of this invention is to provide a photothermal dual-response self-healing ionic liquid-amine complex CO2 absorbent, comprising 1-octyl-3-methylimidazolium thiocyanate ([C8mim][SCN]), a dynamic covalent amine containing a catechol group, boric acid or a boric acid derivative, an active amine, and water. The dynamic covalent amine forms a reversible borate ester bond with boric acid through the catechol group. Under illumination, the photothermal salt converts light energy into heat energy, driving the hydrolysis-reformation or transesterification of the borate ester bond, thereby achieving network reconstruction and performance recovery. By introducing 1-octyl-3-methylimidazolium thiocyanate into the liquid absorber as an endogenous photothermal component, the absorber can self-heat to 60-95°C under light irradiation, driving CO2 desorption and dynamic bond reconstruction without external steam heating, thus significantly reducing regeneration energy consumption. Simultaneously, it solves the problem of insufficient long-term operational stability of the absorber. The reversible boronic acid ester bond dynamic exchange mechanism allows the absorber to repair network defects caused by oxidation, shearing, or phase separation during each light irradiation heating process, restoring absorption capacity and fluidity. It also addresses the difficulty of photothermal materials... To address the issue of coupling with the internal chemical processes of liquid absorbents, 1-octyl-3-methylimidazolium thiocyanate exists in the homogeneous system as a soluble ionic liquid, fundamentally avoiding the sedimentation, agglomeration, and wear of solid photothermal particles; and to address the issue that dynamic covalent self-healing materials have not yet been converted into CO2 liquid absorbent systems, by introducing the dynamic covalent structure of catechol-boron ester into liquid amine absorbents and controlling the low crosslinking density, gelation, amine group encapsulation, and excessive viscosity increase are avoided, enabling the system to maintain flowability and pumpability while possessing self-healing capabilities.

[0021] Furthermore, by limiting the mass percentage range of each component, it is ensured that the amount of photothermal salt added is sufficient to provide adequate heat output under light irradiation (2~40 wt%), while also guaranteeing that the ratio of dynamic amine and boric acid can form an effective dynamic covalent network (synergistic effect of 0.1~20 wt% dynamic amine and 0.02~10 wt% boric acid). Simultaneously, the content of active amine is maintained at a level sufficient to ensure rapid CO2 chemical absorption (5~35 wt%), and the water content ensures good flowability and mass transfer performance (20~80 wt%). The introduction of additives provides room for further optimization of long-term stability. Within this range, the absorbent can effectively heat up and drive dynamic bond reconstruction under light irradiation, while maintaining appropriate viscosity and absorption capacity, thereby solving the two major problems of regeneration energy consumption and cycle stability.

[0022] Furthermore, the molar ratio of boron to catechol groups (B / Cat) was limited to 0.05–1.20, and the molar ratio of dynamic covalent amine to active amine was limited to 0.005–0.30. When B / Cat was below 0.05, the crosslinking density of the borate ester was too low, and the dynamic network was insufficient to provide effective self-healing ability (in Comparative Example 4, when B / Cat=0.007, the absorption capacity was only 68% after 50 cycles). When B / Cat was above 1.20, the excessive crosslinking density led to a sharp increase in viscosity (in Comparative Example 3, when B / Cat=2.4, the viscosity reached 185 mPa·s at 40℃), the amine groups were over-encapsulated, and the CO2 absorption load decreased significantly to 0.18 mol CO2 / mol Amine. The range of 0.05–1.20 ensured that the system was in a "low crosslinking density flowable dynamic network" state, possessing both self-healing ability and gas-liquid mass transfer efficiency. A molar ratio of 0.005 to 0.30 for dynamic covalent amines balances the two requirements of "sufficient self-repairing sites" and "not significantly reducing the contribution of rapid absorption by active amines." If the ratio is too low, the self-repairing sites are insufficient to repair network defects. If the ratio is too high, the steric hindrance and hydrogen bonding of the dynamic amines may obscure the amino sites of the active amines and increase the viscosity of the system.

[0023] Furthermore, the preferred dynamic covalent amine is N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine. This compound integrates four functions in the same molecule: (1) catechol group: forms a reversible borate ester bond with boric acid, endowing the system with light-triggered self-healing ability; (2) tertiary amine structure: promotes CO2 hydration to generate HCO3. -(2) Assists CO2 absorption, compensating for the capacity loss of some active amines after being embedded in the dynamic network; (3) Hydroxyethyl structure: improves the compatibility of the aqueous phase and participates in the hydrogen bond network, which is beneficial to maintaining the homogeneity and fluidity of the system; (4) Aromatic ortho-diol structure: provides free radical scavenging and auxiliary antioxidant functions, directly alleviating the oxidative degradation problem of MEA. This compound realizes the multifunctional integration of "dynamic bond site + CO2 absorption site + hydrophilic structure + antioxidant function", which is a bridge connecting photothermal conversion components and active amines, and is also the material basis for realizing the autonomous cycle of "light self-repair ~ dark absorption".

[0024] Furthermore, the absorbent's pH value is limited to 8.5–11.5, and its viscosity at 40°C is ≤80 mPa·s. The reversible borate ester bond formation reaction between boric acid and catechol is highly sensitive to pH. The weakly alkaline pH range of 8.5–11.5 ensures the effective formation and dynamic reversibility of the borate ester bond. At excessively low pH, the borate ester is easily hydrolyzed, resulting in insufficient network stability; at excessively high pH, ​​the volatility, corrosiveness, and risk of side reactions of the MEA increase. More importantly, CO2 absorption lowers the system pH, a characteristic utilized in this invention as an auxiliary triggering factor. Under CO2-rich conditions, some borate ester bonds loosen, reducing viscosity and facilitating mass transfer. After CO2 desorption during light regeneration, the pH rises, the borate ester bonds stabilize again, and the network recovers. The viscosity limit of ≤80 mPa·s ensures that the absorbent maintains good pumpable flowability at 40°C, preventing excessive reduction in gas-liquid mass transfer efficiency due to the dynamic network.

[0025] This invention also discloses a CO2 capture method, in which CO2 is absorbed at 20~45℃ under dark / shaded conditions; under light conditions, the temperature is raised to 60~95℃ to drive the reconstruction of borate ester bonds and release CO2; (3) after cooling to 20~45℃, it is recycled. In the low-temperature section, CO2 is fully absorbed by the tertiary amine structure in MEA and dynamic covalent amine; in the high-temperature light-irradiated section, CO2 desorption and dynamic covalent network self-repair are achieved by using the endogenous heating of photothermal salt; and in the cooling section, the borate ester bonds are re-stabilized and the amine groups are re-exposed. This method is different from the traditional two-tower continuous process of "absorption tower-external steam desorption tower". It adopts the spatial or temporal separation mode of "shaded absorption-light regeneration" and uses renewable energy such as sunlight to drive the regeneration process, which fundamentally solves the problem of high regeneration energy consumption.

[0026] This invention also discloses a continuous flow absorption-photoremediation / regeneration device, comprising a light-shielding absorption tower, a rich-liquid buffer tank, a transparent photoremediation / regeneration unit, a CO2 separator, a lean-liquid cooler, and a circulating pump, along with their connections and functional divisions. The light-shielding absorption tower ensures the low-temperature absorption section is unaffected by light, maintaining an absorption temperature of 20-45°C. The transparent photoremediation / regeneration unit, as the core unit, uses quartz, borosilicate glass, or fluoropolymer windows to ensure light transmission, independently completing CO2 desorption and absorbent self-remediation under illumination. The CO2 separator collects the desorbed high-purity CO2 product. The lean-liquid cooler cools the regenerated absorbent and returns it to the absorption tower for recycling. This device achieves spatial decoupling and continuous operation of the two core functions of absorption and photoremediation / regeneration, ensuring the absorption section always maintains low-temperature absorption conditions, and the photoregeneration section is not limited by absorption balance, thus solving the engineering requirement for continuous operation in industrial flue gas capture. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of the composition and structure of the compound absorbent of the present invention; Figure 2 This is a schematic diagram of the CO2 absorption mechanism of the compound absorbent of the present invention under dark conditions; Figure 3 This is a schematic diagram of the photothermal heating and dynamic bond reconstruction of the compound absorbent of the present invention under light irradiation conditions; Figure 4 The curves showing the changes in temperature, CO2 loading, and self-repair rate during the circulation of the compound absorbent of this invention are shown. Figure 5 This is a schematic diagram of the continuous flow absorption-photorepair / regeneration device of the present invention. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of the present invention clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention; that is, the described embodiments are only a part of the embodiments of the present invention, and not all of them.

[0029] The detailed description of the embodiments of the present invention provided in the following figures is not intended to limit the scope of the claimed invention, but merely to illustrate one selected embodiment of the invention. All other embodiments obtained by those skilled in the art based on the figures and embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0030] This invention discloses a photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent, the preparation method of which includes the following steps: 1-Octyl-3-methylimidazolium thiocyanate ([C8mim][SCN]), a dynamic covalent amine, boric acid or a boric acid derivative, an active amine, and water are mixed in a predetermined ratio and stirred at 20-40°C until a homogeneous liquid is formed. The pH is then adjusted to 8.5-11.5 with an alkaline solution (such as NaOH or KOH solution) to obtain the compound absorbent.

[0031] This invention preferably uses [C8mim][SCN] as the thermally convertible ionic liquid, whose structure consists of a 1-octyl-3-methylimidazolium cation and a thiocyanate anion. This ionic liquid performs at least the following functions in this invention: 1. As a low-volatility liquid medium, it reduces the overall volatilization loss of the absorbent; 2. Through imidazole cations, octyl chains, and SCN - Photothermal conversion is achieved through vibrational absorption / weak absorption at the tail end; 3. Adjusting the polarity, viscosity, and microphase structure of the system; 4. It forms a homogeneous or micro-phase uniform dispersion system with dynamic covalent amines, MEA, and water.

[0032] The preferred dynamic covalent amine is N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine, whose molecular structure simultaneously possesses a catechol group (which can form a reversible borate ester bond with boric acid) and a tertiary amine structure (which can promote CO2 hydration to HCO3-). 3- ), hydroxyethyl structure (enhancing aqueous compatibility and participating in hydrogen bonding networks) and aromatic ortho-diol structure (providing free radical scavenging and auxiliary antioxidant functions).

[0033] The boric acid or boric acid derivative is selected from one or more of boric acid, borax, phenylboronic acid, 3-aminophenylboronic acid, 4-carboxyphenylboronic acid, and phenyldiboronic acid.

[0034] The active amine is selected from one or more of ethanolamine (MEA), diethanolamine (DEA), N-methyldiethanolamine (MDEA), 2-amino-2-methyl-1-propanol (AMP), and piperazine (PZ).

[0035] The total hemispherical transmittance T(λ) and total hemispherical reflectance R(λ) of the absorbent of this invention in the wavelength range of 300–2500 nm were determined using a UV–Vis–NIR spectrophotometer (equipped with an integrating sphere accessory). The sample was placed in a quartz sample cell with an optical path of 2 mm. Baseline correction was performed for transmittance measurements using a quartz sample cell with the same optical path containing deionized water or a suitable solvent. The obtained spectrum was weighted and integrated according to the AM1.5G solar spectrum (ASTM G173-03) to calculate the solar spectral weighted effective absorbance A. solarThe AM1.5G spectrum was weighted and integrated in the 800–2500 nm band. R(λ) and T(λ) were both expressed as dimensionless values ​​between 0 and 1. The spectral absorbance α(λ) of the sample at wavelength λ was calculated using the following formula: α(λ)=1 R(λ) T(λ) The AM1.5G global hemispherical solar spectral irradiance I is specified using ASTM G173-23. AM1.5G (λ) Perform a weighted integral on the obtained spectral absorbance to calculate the solar spectral weighted absorbance A in the range of 300–2500 nm. solar :

[0036] And calculate the near-infrared spectral weighted absorbance A in the range of 800–2500 nm. NIR :

[0037] Among them, I AM1.5G (λ) represents the AM1.5G standard solar spectral irradiance, R(λ) represents the total reflectance, T(λ) represents the total transmittance, and α(λ) represents the spectral absorbance of the sample.

[0038] In this invention, the absorbent has an A content in the range of 300~2500 nm. solar ≥ 0.30, A is preferred solar ≥ 0.45, more preferably A solar ≥ 0.60; A in the range of 800~2500 nm NIR ≥ 0.10, A is preferred NIR ≥ 0.20.

[0039] The following is the CO2 absorption and light-induced self-repair mechanism of this invention: 1. Dark / Low Temperature Absorption Phase The system remains stable at low temperatures between 20 and 45 °C, preferably 30 to 40 °C, under conditions of no strong light or shading. MEA absorbs CO2 primarily through the following pathways:

[0040] The tertiary amine structure in dynamic covalent amines primarily promotes CO2 hydration to form bicarbonate:

[0041] At this point, the borate ester dynamic network is in a low crosslinking density state, which can maintain the fluidity of the liquid and prevent the amine groups from being completely embedded in the network. The target viscosity of the system can be controlled as follows: viscosity at 40 °C ≤ 80 mPa·s; preferably ≤ 50 mPa·s; more preferably ≤ 25 mPa·s.

[0042] The CO2 absorption load α can be defined as: α = n(CO2absorbed) / n(total amine nitrogen) The preferred absorption phase α is 0.20~0.70 mol CO2 / mol Amine, more preferably 0.35~0.55 mol CO2 / mol Amine.

[0043] 2. Self-repair and partial regeneration stage under light / heating After the CO2-rich absorbent enters the transparent light-based repair module, it is exposed to simulated or natural sunlight. The light intensity is: I = 500~1500 W / m 2 Preferred strength: 800~1200 W / m 2 .

[0044] [C8mim][SCN] absorbs light energy and undergoes nonradiative relaxation, converting the light energy into heat energy, raising the system temperature to 60~95 ​​℃, preferably 70~90 ℃.

[0045] Three types of processes occur after the temperature rises: 1. Partial desorption of CO2: The equilibrium between carbamate and bicarbonate shifts towards the release of CO2; 2. Dynamic exchange of borate ester bonds: B–O bonds undergo hydrolysis-re-esterification, transesterification, and network recombination; 3. Self-repair of unstable structures: Network defects caused by oxidation, local phase separation, mechanical shearing, or changes in CO2 load are rearranged.

[0046] The process of heating up under light can be described by the following energy relationship: m·Cp(dT / dt) = η pt ·I·A irr h·A s ·(T T a ) ε·σ·A s (T 4 T a 4 ) Q des Where m is the mass of the absorbent; Cp is the specific heat capacity of the absorbent; η pt I represents photothermal conversion efficiency; I represents light intensity; A represents the light-thermal conversion efficiency. irr ε is the light-receiving area; h is the convective heat transfer coefficient; ε is the infrared emissivity; σ is the Stefan-Boltzmann constant; Q des The endothermic term for CO2 desorption; T a The ambient temperature.

[0047] To ensure 800~1200 W / m 2 A temperature of 70-90°C under illumination can be achieved through the following parameters working together: 1. The content of [C8mim][SCN] is controlled at 8~25 wt%; 2. The liquid layer thickness should be controlled at 0.5~10 mm, preferably 1~5 mm; 3. The light restoration module uses a transparent quartz, borosilicate glass, or fluoropolymer window; 4. The back panel adopts a low thermal conductivity or selective heat absorption structure; 5. The flow rate should be controlled at 0.1~20 mL / min·cm. 2 The preferred concentration is 0.5~5 mL / min·cm. 2 ; 6. The light exposure time should be controlled between 1 and 60 minutes, preferably between 5 and 30 minutes.

[0048] 3. Cooling / Network Stabilization Phase After the illumination stops or the absorbent leaves the illumination module, the system cools to 25–45 °C via a heat exchanger or natural cooling. The borate ester bonds are restabilized, and the dynamic covalent amine and MEA re-expose absorption sites, allowing the absorbent to enter the next round of CO2 absorption.

[0049] The self-healing mechanism of this invention should not be understood merely as macroscopic crack repair, but rather as the restoration of reversible performance indicators such as viscosity, phase state, and CO2 absorption capacity to their pre-aging state through reversible borate ester exchange and dynamic associative structural rearrangement under photothermal action; it does not include the reverse transformation of irreversible chemical degradation products that have already occurred. Evaluation can be conducted using indicators such as CO2 absorption capacity recovery rate, viscosity recovery rate, phase uniformity, and changes in B–O related spectral peaks.

[0050] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0051] Example 1 (15 wt% MEA - Low photothermal salt / high dynamic network type compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 15 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 5 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 10 wt% Boric acid: 3 wt% Sodium sulfite (antioxidant): 0.5 wt% Benzotriazole (corrosion inhibitor): 0.5 wt% Deionized water: 66.00 wt%.

[0052] During preparation, each component is stirred at 25°C until completely dissolved, and the pH is adjusted to 10.6 with NaOH solution to obtain the 15 wt% MEA-low photothermal salt / high dynamic network type composite absorbent.

[0053] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 1.03, and the molar ratio of the dynamic covalent amine to MEA is approximately 0.193. At 40°C, the viscosity of the absorbent in this embodiment is approximately 78 mPa·s. Its A... solar Approximately 0.34, A NIR It is approximately 0.11.

[0054] Example 2 (15 wt% MEA-high photothermal salt / low dynamic amine boundary type compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 15 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 25 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 1 wt% Boric acid: 0.1 wt% EDTA-Na2 (metal ion chelating agent): 0.01 wt% Deionized water: 58.89 wt%.

[0055] During preparation, each component is stirred at 25°C until completely dissolved, and the pH is adjusted to 9.5 with NaOH solution to obtain the 15 wt% MEA-high photothermal salt / low dynamic amine boundary type compound absorbent.

[0056] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.34, and the molar ratio of the dynamically covalent amine to MEA is approximately 0.019. At 40°C, the viscosity of the absorbent in this embodiment is approximately 30 mPa·s. Its A... solar Approximately 0.65, ANIR It is approximately 0.28.

[0057] Example 3 (18 wt% MEA-medium-low photothermal salt type compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 18 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 12 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 4 wt% Boric acid: 0.5 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.2 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 65.00 wt%.

[0058] During preparation, each component is stirred at 25°C until completely dissolved, and the pH is adjusted to 10.0 with NaOH solution to obtain the 18 wt% MEA-medium low photothermal salt type compound absorbent.

[0059] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.43, and the molar ratio of the dynamically covalent amine to MEA is approximately 0.064. At 40°C, the viscosity of the absorbent in this embodiment is approximately 38 mPa·s. Its A... solar Approximately 0.44, A NIR It is approximately 0.16.

[0060] Example 4 (18 wt% MEA-medium-high photothermal salt / enhanced self-healing compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 18 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 18 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 6 wt% Boric acid: 0.8 wt% EDTA-Na2 (metal ion chelating agent): 0.3 wt% Sodium sulfite (antioxidant): 0.2 wt% Benzotriazole (corrosion inhibitor): 0.2 wt% Deionized water: 56.50 wt%.

[0061] During preparation, all components are stirred at 25°C until completely dissolved, and the pH is adjusted to 10.2 with NaOH solution to obtain the 18 wt% MEA-medium high photothermal salt / enhanced self-healing compound absorbent.

[0062] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.46, and the molar ratio of the dynamically covalent amine to MEA is approximately 0.096. At 40°C, the viscosity of the absorbent in this embodiment is approximately 52 mPa·s. Its A... solar Approximately 0.55, A NIR It is approximately 0.22.

[0063] Example 5 (20 wt% MEA-medium low photothermal salt / low viscosity compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 20 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 12 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 3 wt% Boric acid: 0.5 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.2 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 64.00 wt%.

[0064] During preparation, all components are stirred at 25°C until completely dissolved, and the pH is adjusted to 10.0 with NaOH solution to obtain the 20 wt% MEA-medium low photothermal salt / low viscosity compound absorbent.

[0065] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.57, and the molar ratio of the dynamically covalent amine to MEA is approximately 0.043. At 40°C, the viscosity of the absorbent in this embodiment is approximately 35 mPa·s. Its A... solar Approximately 0.45, A NIR It is approximately 0.16.

[0066] Example 6 (20 wt% MEA-medium-high photothermal salt / high cycling stability compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 20 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 18 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 5 wt% Boric acid: 0.8 wt% EDTA-Na2 (metal ion chelating agent): 0.3 wt% Sodium sulfite (antioxidant): 0.2 wt% Benzotriazole (corrosion inhibitor): 0.2 wt% Deionized water: 55.50 wt%.

[0067] During preparation, each component is stirred at 25°C until completely dissolved, and the pH is adjusted to 10.2 with NaOH solution to obtain the 20 wt% MEA-medium high photothermal salt / high cycle stability compound absorbent.

[0068] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.55, and the molar ratio of the dynamic covalent amine to MEA is approximately 0.072. At 40°C, the viscosity of the absorbent in this embodiment is approximately 48 mPa·s. Its A... solar Approximately 0.56, A NIR It is approximately 0.23.

[0069] Example 7 (23 wt% MEA-optimized compound absorbent) The following components are formulated according to mass percentage: MEA (active amine): 23 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 15 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 4 wt% Boric acid: 0.6 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.1 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 57.00 wt%.

[0070] During preparation, each component is stirred at 25°C until completely dissolved, and the pH is adjusted to 10.0 with NaOH solution to obtain the 23 wt% MEA-comprehensive preferred compound absorbent.

[0071] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.51, and the molar ratio of the dynamically covalent amine to MEA is approximately 0.050. At 40°C, the viscosity of the absorbent in this embodiment is approximately 42 mPa·s. Its A...solar Approximately 0.50, A NIR It is approximately 0.20.

[0072] Example 8 (25 wt% MEA - High Concentration Boundary-Type Compound Absorbent) The following components are formulated according to mass percentage: MEA (active amine): 25 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 25 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 10 wt% Boric acid: 3 wt% EDTA-Na2 (metal ion chelating agent): 1 wt% Sodium sulfite (antioxidant): 0.5 wt% Benzotriazole (corrosion inhibitor): 0.5 wt% Deionized water: 35.00 wt%.

[0073] During preparation, each component is stirred at 30°C until completely dissolved, and the pH is adjusted to 10.8 with NaOH solution to obtain the 25 wt% MEA-high concentration boundary-type compound absorbent.

[0074] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 1.03, and the molar ratio of the dynamically covalent amine to MEA is approximately 0.116. At 40°C, the viscosity of the absorbent in this embodiment is approximately 78 mPa·s. Its A... solar Approximately 0.69, A NIR It is approximately 0.30.

[0075] Comparing the MEA concentration, photothermal heating, CO2 absorption load, viscosity at 40°C, cycle capacity retention, and self-healing rate of Examples 1 to 8, Example 7 maintained a high CO2 absorption capacity and photothermal regeneration capability while keeping viscosity and water content within a suitable range. Therefore, Example 7 was selected as the basis for the preferred formulation in the main amine type comparison experiment. Although Example 8 had higher MEA and [C8mim][SCN] content, its dynamic amine, boric acid, and additives were all close to the upper limit, its water content was at the lower limit, and its viscosity was close to the upper limit. Therefore, it was not used as the basis for subsequent screening of different main amine types.

[0076] Example 9 (DEA main amine comparative compound absorbent) The following components are formulated according to mass percentage: DEA (active amine): 23 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 15 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 4 wt% Boric acid: 0.6 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.1 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 57.00 wt%.

[0077] The preparation method is the same as in Example 7, except that 23 wt% of MEA is replaced with DEA, while the other components and contents remain unchanged, and the pH is adjusted to 10.0 with NaOH solution.

[0078] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.51, and the molar ratio of the dynamically covalent amine to DEA is approximately 0.087. At 40°C, the viscosity of the absorbent in this embodiment is approximately 45 mPa·s. Its A... solar Approximately 0.50, A NIR It is approximately 0.20.

[0079] Example 10 (MDEA main amine comparative compound absorbent) The following components are formulated according to mass percentage: MDEA (active amine): 23 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 15 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 4 wt% Boric acid: 0.6 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.1 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 57.00 wt%.

[0080] The preparation method is the same as in Example 7, except that 23 wt% of MEA is replaced with MDEA, while the other components and contents remain unchanged, and the pH is adjusted to 10.0 with NaOH solution.

[0081] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.51, and the molar ratio of the dynamically covalent amine to MDEA is approximately 0.098. At 40°C, the viscosity of the absorbent in this embodiment is approximately 43 mPa·s. Its A... solar Approximately 0.50, A NIR It is approximately 0.20.

[0082] Example 11 (AMP main amine comparative compound absorbent) The following components are formulated according to mass percentage: AMP (Active Amine): 23 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 15 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 4 wt% Boric acid: 0.6 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.1 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 57.00 wt%.

[0083] The preparation method is the same as in Example 7, except that 23 wt% of MEA is replaced with AMP, while the other components and contents remain unchanged, and the pH is adjusted to 10.0 with NaOH solution.

[0084] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.51, and the molar ratio of the dynamically covalent amine to AMP is approximately 0.073. At 40°C, the viscosity of the absorbent in this embodiment is approximately 44 mPa·s. Its A... solar Approximately 0.50, A NIR It is approximately 0.20.

[0085] Example 12 (PZ main amine comparative compound absorbent) The following components are formulated according to mass percentage: PZ (active amine): 23 wt% [C8mim][SCN] (Photothermal conversion ionic liquid): 15 wt% N-(3,4-Dihydroxyphenylethyl)-N-methylethanolamine (dynamic covalent amine): 4 wt% Boric acid: 0.6 wt% EDTA-Na2 (metal ion chelating agent): 0.2 wt% Sodium sulfite (antioxidant): 0.1 wt% Benzotriazole (corrosion inhibitor): 0.1 wt% Deionized water: 57.00 wt%.

[0086] The preparation method is the same as in Example 7, except that 23 wt% of MEA is replaced with PZ, while the other components and contents remain unchanged, and the pH is adjusted to 10.0 with NaOH solution.

[0087] Calculations show that in this embodiment, the molar ratio of boron to catechol groups (B / Cat) is approximately 0.51, and the molar ratio of the dynamically covalent amine to PZ is approximately 0.071. At 40°C, the viscosity of the absorbent in this embodiment is approximately 50 mPa·s. Its A... solar Approximately 0.50, A NIR It is approximately 0.20.

[0088] The following is an experiment on CO2 absorption and light self-repair in this invention.

[0089] Experimental Method: Any one of the compound absorbents from Examples 1-12 above was used. When comparing different examples, the gas composition, liquid layer thickness, irradiation intensity, and temperature conditions were kept consistent. A 15 vol% CO2 / N2 mixture was bubbled through at 40°C for absorption, and the CO2 absorption loading was recorded. After absorption saturation, the CO2-rich absorbent was placed in a transparent quartz irradiation cell (liquid layer thickness 2 mm) and irradiated at 1000 W / m². 2 Simulated sunlight exposure was used to record temperature changes over time and CO2 desorption. After the sunlight exposure ended, the absorbent was cooled to 40°C, and a 15 vol% CO2 / N2 mixture was introduced again for the next round of absorption. The absorption capacity and viscosity changes were recorded.

[0090] CO2 absorption loading α is defined as: α = n(CO2absorbed) / n(total amine nitrogen) Photothermal heating performance: At 1000 W / m 2 Under simulated sunlight irradiation (liquid layer thickness 2 mm), the temperature rise of each embodiment is as follows: Taking the absorbents of Examples 1-12 as examples, at 1000 W / m 2Under simulated sunlight irradiation (liquid layer thickness 2 mm), Example 1: approximately 65°C / 25 min; Example 2: approximately 89°C / 10 min; Example 3: approximately 76°C / 17 min; Example 4: approximately 83°C / 13 min; Example 5: approximately 77°C / 16 min; Example 6: approximately 84°C / 12 min; Example 7: approximately 81°C / 14 min; Example 8: approximately 90°C / 9 min. Examples 9-12 used the same [C8mim][SCN], dynamic covalent amine, boric acid, additives, and water content as Example 7, only changing the main amine type. Their photothermal heating performance was close to that of Example 7, approximately 80°C / 14 min, 81°C / 14 min, 81°C / 14 min, and 80°C / 15 min, respectively. These results indicate that the absorbent of the present invention operates at 800-1200 W / m 2 Under light conditions, it can effectively heat up to 60~95℃, and the heating rate and equilibrium temperature are positively correlated with the [C8mim][SCN] content.

[0091] CO2 absorption performance: Under conditions of 40℃ and 15 vol% CO2 / N2, the CO2 absorption loading α of Examples 1-8 were approximately 0.34, 0.35, 0.38, 0.39, 0.42, 0.43, 0.47, and 0.49 mol CO2 / mol Amine, respectively. Therefore, in this group of MEA main amine screening examples, the CO2 absorption loading generally showed a positive correlation with the increase of MEA mass fraction from 15 wt% to 25 wt%. In the two sets of examples with the same MEA concentration, the loading showed only slight differences due to differences in [C8mim][SCN], dynamic covalent network density, and viscosity. In Examples 9-12, the main amine concentration was 23 wt%, and only the main amine type was changed. The CO2 absorption loading α was approximately 0.46, 0.50, 0.51, and 0.49 mol CO2 / mol Amine, respectively, reflecting the differences in absorption reaction pathways and capacities of different amine types. Cyclic stability: Using the absorbents of Examples 1-12, after 50 cycles of "dark absorption-light regeneration", the CO2 absorption capacity retention rates were approximately 86%, 82%, 89%, 92%, 90%, 93%, 94%, 89%, 93%, 95%, 94%, and 93%, respectively. Among them, Example 7 achieved a good balance between MEA concentration, photothermal salt content, dynamic network density, and viscosity, with a capacity retention rate of approximately 94% after 50 cycles. Example 8, due to its high photothermal salt content, high dynamic amine content, and low water content, had a viscosity close to the upper limit. Although it had a high initial absorption capacity, the mass transfer and pumping margins during long-term cycling were relatively small.

[0092] Self-healing performance: The absorbents from Examples 1-12 were accelerated to age at 60°C for 48 h, and then subjected to an aging process of 1000 W / m 2 Self-repair was performed under simulated sunlight exposure for 20 minutes, with self-repair rates of approximately 88%, 79%, 89%, 92%, 88%, 93%, 94%, 90%, 93%, 94%, 94%, and 93%, respectively. When the dynamic covalent amine content was too low, there were insufficient reversible borate sites, while an excessively dense dynamic network with high viscosity might limit rapid network rearrangement. The moderate dynamic covalent amine and B / Cat levels corresponding to Example 7 showed a better overall self-repair effect.

[0093] The following is a performance evaluation of several aspects of the present invention.

[0094] 1. Photothermal heating capacity test Take 50 mL of each absorbent from Examples 1-12 and place them in a transparent quartz petri dish with an inner diameter of 5 cm (the liquid layer thickness is about 2 mm). Incubate under AM1.5G simulated sunlight (1000 W / m²). 2 The liquid was irradiated with infrared thermal imager to record the temperature changes at the liquid surface. Examples 2, 4, 6, 7, 8 and Examples 9-12 could reach or approach 80°C within about 15 minutes. Among them, Examples 2 and 8 had the fastest heating rate due to their high [C8mim][SCN] content.

[0095] 2. CO2 absorption capacity test A bubbling absorption device was used, and a 15 vol% CO2 / N2 mixture was introduced at 200 mL / min at 40°C. The CO2 concentration in the outlet gas was measured using an online CO2 concentration analyzer, and the absorption capacity was calculated. The CO2 absorption load α in Examples 1-8 increased overall with the MEA mass fraction, ranging from approximately 0.34 to 0.49 mol CO2 / mol Amine; Example 7 achieved approximately 0.47 mol CO2 / mol Amine, while also considering gas-liquid mass transfer and subsequent photothermal regeneration under low viscosity conditions. Examples 9-12 were used to compare different main amine types; under the same main amine concentration and other formulation conditions, the α test results were approximately 0.46 to 0.51 mol CO2 / mol Amine.

[0096] 3. Cyclic capacity retention test The absorbents of Examples 1-12 were subjected to dark absorption-light regeneration cycle tests. After 50 cycles, the absorption capacity retention rate was approximately 82%-95%, with Examples 4, 6, 7 and Examples 9-12 maintaining a retention rate above 92%. Example 7, as the optimal formulation, showed a capacity retention rate of approximately 94% after 50 cycles.

[0097] 4. Viscosity recovery rate test Taking the optimized absorbent of Example 7 as an example, after accelerated aging at 60°C for 72 h, the viscosity at 40°C increased from approximately 42 mPa·s to approximately 64 mPa·s; after 1000 W / m 2 After 25 minutes of simulated sunlight exposure, the viscosity recovered to approximately 45 mPa·s, while the CO2 absorption capacity recovered to 94% of its initial value. Examples 9-12, with the same content of dynamic covalent amine, boric acid, and photothermal salt as Example 7, generally exhibited self-repair rates in the range of 93%–94%.

[0098] 5. MEA Degradation Inhibition Rate Test The degradation products of Example 7 (containing dynamic covalent amine and additives) and the control system without dynamic covalent amine were quantitatively analyzed under the same conditions using ion chromatography and LC-MS. The formation rate of the main MEA degradation products in Example 7 was lower than that in the control system without dynamic covalent amine.

[0099] The following are comparative examples that contrast with embodiments of the present invention.

[0100] Comparative Example 1 (excluding dynamic covalent amines and boric acid) Prepare by weight percentage: MEA 20 wt%, [C8mim][SCN] 10 wt%, deionized water 70 wt%. The preparation method is the same as in Example 1.

[0101] At 40℃ and 15 vol% CO2 / N2, the CO2 absorption loading α of this absorbent is 0.44 mol CO2 / mol Amine. After 1000 W / m 2 After 20 minutes of simulated sunlight exposure, the temperature rose to 76°C, but the CO2 desorption capacity was only about 60% of that in Example 1. After 50 cycles, the absorption capacity decreased to 65% of the initial value, far lower than the 86% in Example 1. This indicates that without dynamic covalent amines and boric acid, the system lacks self-healing ability, and the cycle stability is significantly reduced.

[0102] Comparative Example 2 (excluding [C8mim][SCN]) Prepare by weight percentage: MEA 20 wt%, N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine 3 wt%, boric acid 0.5 wt%, deionized water 76.5 wt%. The preparation method is the same as in Example 1.

[0103] At 1000 W / m 2Under simulated sunlight irradiation (liquid layer thickness 2 mm), the absorbent's temperature only increased from 25°C to 42°C within 30 minutes, failing to reach the temperature (60–95°C) required to trigger dynamic exchange of borate ester bonds. After 50 cycles, the absorption capacity decreased to 70% of the initial value, indicating limited self-healing effect. This demonstrates that without [C8mim][SCN], the system lacks endogenous photothermal conversion capability and cannot effectively drive the self-healing process.

[0104] Comparative Example 3 (B / Cat ratio is too high) Prepare by weight percentage: MEA 15 wt%, [C8mim][SCN] 10 wt%, N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine 2 wt%, boric acid 2.5 wt%, deionized water 70.5 wt%. The preparation method is the same as in Example 1.

[0105] Calculations showed that the B / Cat ratio in this comparative example was approximately 2.4. During the preparation process, the system viscosity increased significantly, reaching 185 mPa·s at 40℃, far exceeding the acceptable upper limit of 80 mPa·s, indicating poor flowability and impaired gas-liquid mass transfer. The CO2 absorption loading α was only 0.18 mol CO2 / mol Amine. This indicates that when the B / Cat ratio is too high, excessive cross-linking leads to amine group encapsulation and decreased mass transfer.

[0106] Comparative Example 4 (B / Cat ratio too low) Prepared by weight percentage: MEA 22 wt%, [C8mim][SCN] 10 wt%, N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine 5 wt%, boric acid 0.02 wt%, deionized water 62.98 wt%. The preparation method is the same as in Example 1.

[0107] Calculations showed that the B / Cat ratio in this comparative example was approximately 0.007. Although the system viscosity was low (approximately 28 mPa·s at 40°C), the absorption capacity decreased to 68% of the initial value after 50 cycles, indicating a weak self-healing effect. This suggests that when the B / Cat ratio is too low, the dynamic network is insufficient to provide effective self-healing capabilities.

[0108] like Figure 1As shown, the compound absorbent of this invention is a homogeneous liquid system, mainly composed of the following components: 1-octyl-3-methylimidazolium thiocyanate ([C8mim][SCN]) as the photothermal conversion ionic liquid component, uniformly dispersed throughout the liquid phase system; conventional active amines such as MEA as fast CO2 absorption components; dynamic covalent amines such as N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine, which form reversible borate ester bonds with boric acid or boric acid derivatives through their catechol groups, constituting a dynamic covalent network with low crosslinking density; and water as the mass transfer medium. The components are uniformly mixed at the molecular level to form a flowable liquid reaction medium. [C8mim][SCN] simultaneously serves as the liquid phase medium, photothermal conversion, and microenvironment regulation function; the dynamic covalent amines introduce dynamic network characteristics into the liquid absorbent system through reversible borate ester bonds.

[0109] like Figure 2 As shown, under dark or light-blocking conditions, with the system temperature maintained between 20 and 45°C (preferably 30 to 40°C), the dynamic borate ester network remains in a low crosslinking density state, maintaining good liquid flowability. MEA primarily absorbs CO2 through the following pathways: This leads to the formation of carbamates. The tertiary amine structure in dynamically covalent amines primarily promotes CO2 hydration to form bicarbonates. At this point, the active amino groups in the dynamic covalent amine remain exposed and can effectively participate in CO2 absorption; the reversible borate ester bonds are in a relatively stable low-crosslinking state and do not hinder gas-liquid mass transfer.

[0110] like Figure 3 As shown, under illumination conditions (light intensity 500~1500 W / m²), 2 Preferred strength: 800~1200 W / m 2 [C8mim][SCN] absorbs light energy and converts it into heat energy through nonradiative relaxation, raising the system temperature to 60~95℃ (preferably 70~90℃). After heating, three types of synergistic processes occur: (1) partial desorption of CO2: the equilibrium of carbamate and bicarbonate shifts towards the release of CO2; (2) dynamic exchange of boronic acid ester bonds: hydrolysis-re-esterification, ester exchange, and network recombination of BO bonds occur; (3) self-repair of unstable structures: network defects caused by oxidation, local phase separation, or changes in CO2 loading are rearranged. Through the above synergistic effects, the system completes dynamic network reconstruction and performance recovery while releasing CO2.

[0111] like Figure 4As shown, the horizontal axis represents the cycle time, and the vertical axis corresponds to temperature (curve A), CO2 loading (curve B), and self-repair rate (curve C), respectively. In a complete cycle: (1) Dark absorption stage (t0~t1): The system is at a low temperature (25~45℃), and the CO2 loading gradually increases to 0.35~0.55 mol CO2 / mol Amine; (2) Light regeneration / self-repair stage (t1~t2): The system is heated to 60~95℃ under light, the CO2 loading decreases (CO2 is released), and the self-repair rate increases; (3) Cooling stabilization stage (t2~t3): The system cools down, the borate ester bonds are re-stabilized, and self-repair is completed. After multiple cycles, the CO2 loading and self-repair rate remain stable, indicating that the system has good cycle stability. Specifically, taking the absorbent of the comprehensively preferred Example 7 as an example, after 50 cycles, the CO2 absorption capacity retention rate is about 94%, and the self-repair rate (in terms of capacity) is about 94%; after 200 cycles, the absorption capacity retention rate can still be maintained at about 85%.

[0112] like Figure 5 As shown, this invention also provides a continuous flow CO2 capture device, including a light-shielding absorption tower, a rich liquid buffer tank, a transparent light-irradiated repair / regenerator, a CO2 separator, a lean liquid cooler, and a circulation pump. CO2-containing gas enters the light-shielding absorption tower through the gas inlet and comes into countercurrent contact with the absorbent sprayed from the top of the tower. After the CO2 is absorbed, the purified gas is discharged from the gas outlet. The CO2-rich absorbent enters the transparent light-irradiated repair / regenerator through the rich liquid buffer tank, where it is heated to 60-95°C under light irradiation, resulting in CO2 desorption and borosilicate bond reconstruction. The desorbed CO2 is collected from the CO2 product outlet through the CO2 separator. The regenerated lean liquid is cooled to 20-45°C by the lean liquid cooler and then returned to the light-shielding absorption tower for recycling by the circulation pump. The window material of the transparent light-irradiated repair / regenerator is quartz, borosilicate glass, or fluoropolymer, the liquid layer thickness is 0.5-10 mm (preferably 1-5 mm), and the absorbent flow rate is 0.1-20 mL / min·cm. 2 (Preferred concentration: 0.5~5 mL / min·cm) 2 The light exposure time is 1~60 min (preferably 5~30 min). This device can achieve spatial separation between the absorption section and the light repair section, and can operate continuously.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the present invention.

Claims

1. A photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent, characterized in that, include: 1-Octyl-3-methylimidazolium thiocyanate, a dynamic covalent amine containing a catechol group, boric acid or a boric acid derivative, an active amine, and water; The dynamic covalent amine forms a reversible borate bond with boric acid or boric acid derivatives through the catechol group; The 1-octyl-3-methylimidazolium thiocyanate converts light energy into heat energy under illumination to drive the reversible borate ester bond to undergo hydrolysis-reformation or transesterification reactions, thereby achieving internal network reconstruction of the absorbent and restoration of CO2 absorption performance.

2. The photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to claim 1, characterized in that, The absorbent comprises, by weight percentage: 1-Octyl-3-methylimidazolium thiocyanate: 2~40 wt% Dynamic covalent amines: 0.1~20 wt% Boric acid or boric acid derivatives: 0.02~10 wt% Active amines: 5~35 wt% Water: 20~80 wt% Additives: 0~5 wt%.

3. The photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to claim 2, characterized in that, The absorbent comprises, by weight percentage: 1-Octyl-3-methylimidazolium thiocyanate: 5~25 wt% Dynamic covalent amines: 1~10 wt% Boric acid or boric acid derivatives: 0.1~3 wt% Active amine: 15~25 wt% Water: 35~65 wt% Additives: 0.01~2 wt%.

4. The photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to any one of claims 1 to 3, characterized in that, The molar ratio (B / Cat) of boron to catechol groups in boric acid or boric acid derivatives is 0.05~1.20; The molar ratio of the dynamic covalent amine to the active amine is 0.005~0.

30.

5. The photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to any one of claims 1 to 3, characterized in that, The additive is selected from one or more of antioxidants, metal ion chelators, corrosion inhibitors, defoamers, pH buffers, or photothermal enhancers; The dynamic covalent amine is N-(3,4-dihydroxyphenylethyl)-N-methylethanolamine.

6. The photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to any one of claims 1 to 3, characterized in that, The absorbent has a pH value of 8.5~11.5; The absorbent has a viscosity of ≤80 mPa·s at 40°C.

7. The photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to any one of claims 1 to 3, characterized in that, The active amine is one or more of ethanolamine, diethanolamine, N-methyldiethanolamine, 2-amino-2-methyl-1-propanol, and piperazine.

8. A CO2 capture method, characterized in that, Using the photothermal dual-response self-healing ionic liquid-amine composite CO2 absorbent according to any one of claims 1 to 7 includes the following steps: (1) Under dark or light-proof conditions, the absorbent is brought into contact with CO2-containing gas at 20~45℃ to absorb CO2 and obtain a CO2-rich absorbent; (2) The CO2-rich absorbent is placed under light conditions to cause 1-octyl-3-methylimidazolium thiocyanate to undergo photothermal conversion and be heated to 60~95℃, thereby driving the reconstruction of borate ester bonds and releasing some CO2. (3) Cool the absorbent after releasing CO2 to 20~45℃ and return to step (1) for recycling.

9. The CO2 capture method according to claim 8, characterized in that, In step (2), the illumination intensity is 500~1500 W / m². 2 The illumination time is 1~60 min, and the liquid layer thickness of the CO2-rich absorbent is 0.5~10 mm.

10. A continuous flow absorption-photoremediation / regeneration apparatus for implementing the CO2 capture method of claim 8 or 9, characterized in that, include: The light-shielding absorption tower is used to make the absorbent come into countercurrent contact with CO2-containing gas, and to absorb CO2 at 20~45℃ under dark or light-shielding conditions. A rich liquid buffer tank, connected to the bottom of the light-shielding absorption tower, is used to receive CO2-rich absorbent; A transparent light-induced repair / regenerator is connected to the outlet of the rich liquid buffer tank. It is used to heat the CO2-rich absorbent to 60~95°C under light conditions, while simultaneously completing CO2 desorption and internal network reconstruction of the absorbent. A CO2 separator, connected to the gas outlet of the transparent light-induced repair / regenerator, is used to separate and collect the desorbed CO2; A lean liquid cooler, connected to the liquid outlet of the transparent light-induced repair / regeneration device, is used to cool the regenerated absorbent to 20~45°C. A circulating pump, connected between the outlet of the lean liquid cooler and the top of the light-shielding absorption tower, is used to return the cooled absorbent to the light-shielding absorption tower for recycling.

Citation Information

Patent Citations

  • Functionalized ionic liquid CO2 absorbent capable of realizing low-temperature self-extraction regeneration and application of functionalized ionic liquid CO2 absorbent

    CN116651148A